Perception of essence of controlling and its use in manufacturing enterprises in time of crisis: does controlling fulfill its essence? - Potkány, Marek; Hašková, Simona; Lesníková, Petra; Schmidtová, Jarmila (Journal of Business Economics and Management, 2022)
The use of controlling in the business sphere is relatively broad and its essence can be perceived diversely by enterprises of different sectors and sizes. The aim of the research is to identify the current state of the use of controlling in Slovak manufacturing enterprises with an assessment of the perception of its essence in terms of capital structure and business performance measured by the Return on Sales (ROS). Total of 347 enterprises were asked by means of stratified sampling in 2020. Goodness-of-fit test was used when examining the representativeness of the research sample and for individual hypotheses the two-sample test of relative frequencies, relative frequency test, 95% interval estimates of relative frequencies, contingency and Pearson’s chi-square test were applied. Testing confirmed the existence of statistically significant correlation between the capital structure of manufacturing enterprises and the level of wider perception and practical use of the essence of controlling in relation to the performance measured by ROS. In conclusion is demonstrated that the potential of controlling in enterprises is not fully used, especially in the form of comprehensive secondary coordination of management and the possible directions of using it are outlined, with a positive impact on business performance.